Kajian Yuridis Sanksi Pidana Terhadap Tindak Pidana Hate Speech Cyberbullying di Indonesia - Alhakim, Abdurrakhman; Girsang, Junimart; Wadhi, Getrudis Yetiana (Legalitas: Jurnal Hukum, 2023)
Developments in the field of information and communication technology can have both positive and negative impacts and one of them is cyberbullying. Cyberbullying is a form of intimidation that occurs in cyberspace. The aim of this research is to find out how the criminal law policy for dealing with cyberbullying is based on criminal law reform. Criminal law policies regarding cyberbullying in Indonesia can currently be identified with the Criminal Code and Law no. 11 of 2008 concerning Information and Electronic Transactions. The current Criminal Code contains several articles relating to cyberbullying. Criminal law policies for efforts to overcome cyberbullying to reform criminal law can be obtained through the Concept of the Criminal Code as well as comparative studies with other countries regarding cyberbullying, so that the latest Criminal Code is formed and carried out comparisons so that it can be used as a reference and consideration for providing input on how to overcome cyberbullying in Indonesia. The type of research used is normative juridical using a statutory approach, analytical approach and case approach.